A structurally stable supported Sn-based alloy catalyst and its preparation method and application

The preparation of high-content unsaturated five-coordinated Al2O3-V support through nucleation and crystallization isolation method solves the problem of difficult control of structural stability of bimetallic catalysts during the preparation process, realizes the high activity and selectivity of the catalyst, and meets the precious metals The demand for resource substitution provides a structurally stable supported Sn-based alloy catalyst.

CN116586072BActive Publication Date: 2024-12-24BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310563290.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-18
Publication Date
2024-12-24
Estimated Expiration
2043-05-18

AI Technical Summary

Technical Problem

In the prior art, bimetallic Ni-Sn catalysts are difficult to control the oxidation state of Sn and the structural stability of Ni-Sn nanoparticles during the preparation process, resulting in poor catalyst activity and selectivity, and scarce precious metal resources, and effective replacement is needed. plan.

Method used

Nucleation crystallization isolation method is used to prepare high-content unsaturated five-coordinated Al2O3-V as a carrier, and rapid nucleation and temperature control crystallization are used to regulate the unsaturated coordination structure of the Al2O3 surface to induce Ni and The interaction of Sn forms a highly ordered M-Sn/Al2O3-V catalyst with metal atom arrangement.

Benefits of technology

The structural stability of the catalyst and the orderly arrangement of active metal atoms are achieved, and the activity and selectivity of alkyne selective hydrogenation and alkane selective dehydrogenation reactions are improved. The process is gentle, and the catalyst is easy to recover without surfactants. and reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004235904120000011
    Figure HDA0004235904120000011
  • Figure HDA0004235904120000012
    Figure HDA0004235904120000012
  • Figure HDA0004235904120000013
    Figure HDA0004235904120000013
Patent Text Reader

Abstract

The present invention provides a structurally stable supported Sn-based alloy catalyst and its preparation method and application. 3+ Al 2 O 3‑V As a carrier, it is used as a capture center to load M and Sn precursors. 2 O 3 Under the induction of the surface unsaturated coordination structure, the reduction rate matching of the two metal components was achieved by reduction, and a M-Sn ordered alloy structure catalyst with a stable structure and a specific morphology was obtained, which is represented by M-Sn / Al 2 O 3‑V The active metal M atoms are discontinuous and electron-rich, which solves the problem of Sn and Al in the traditional impregnation synthesis scheme. 2 O 3 The catalyst is suitable for the selective hydrogenation of alkynes and the selective dehydrogenation of alkanes, and has outstanding catalytic performance, high selectivity and good stability, and is easy to recover and reuse.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of traditional petrochemical industry and fine chemical industry, and specifically relates to a structurally stable supported Sn-based alloy catalyst and a preparation method thereof. The catalyst is mainly used for selective hydrogenation of alkynes and selective dehydrogenation of alkanes. Background Art

[0002] More than 50% of the world's precious metals are used to prepare catalysts in chemical processes every year. However, in recent years, precious metal resources have become increasingly scarce, resulting in a widening gap between supply and demand. Therefore, effective substitution of precious metals is very important and urgent. Due to their good ability to dissociate hydrogen, non-precious metals such as Ni are widely used in hydrogenation reactions in chemical industrial processes. Compared with single metal catalysts, alumina-supported bimetallic catalysts with non-precious metal Ni as the active component and main group metal Sn as the promoter show excellent activity and selectivity in the conversion of unsaturated hydrocarbons. This is attributed to the interaction between Ni and Sn to form an alloy after reduction in a hydrogen atmosphere. However, in actual catalytic systems, the oxidation state of Sn in bimetallic Ni-Sn catalysts obtained by different preparation methods and the structural stability of Ni-Sn nanoparticles are difficult to control. In previous reports, Krishnan et al. found in Ag Chemisorption and XPS Study of Bimetallic Pt-Sn / Al2O3 Catalysts, Journal of Catalysis, 1991, 127, 287-306 that in the Al2O3-loaded catalyst prepared by the traditional impregnation method, Sn ions interacted strongly with the Al2O3 surface, thereby forming a tin aluminate complex, resulting in an uneven distribution of Sn and inhibiting the complete reduction of tin oxide. More noteworthy is that due to the lower surface energy, Sn atoms in the Ni-Sn intermetallic nanoparticles are easily segregated and migrated to the catalyst surface under reaction conditions, thereby forming a reconstructed SnO x In view of the problems existing in the above preparation methods, considering the inseparable connection between metal and carrier in supported catalysts, it is of great significance to create new preparation strategies based on the use of industrial Al2O3 as a carrier, induce and restrict the behavior of active metal nucleation and growth, and realize the precise construction and stable control of supported catalyst structure.

[0003] In order to solve this problem, researchers have conducted many studies. For example, Francisco et al. found in Role oftin on the electronic properties of Ni / Al2O3 catalyst and its effect over themethane dry reforming reaction, Applied Catalysis A, General, 2021, 618, 118129 that the use of excess Sn species promotes the formation of M-Sn intermetallic compounds, but the M-Sn atomic ratio cannot be precisely controlled. Lin et al. found in Adhesion and Atomic Structures of Gold on Ceria Nanostructures: The Role of Surface Structure and Oxidation State of Ceria Supports, nanoletters, 2015, 15, 5375-5381 that by regulating the morphology of CeO2 carriers, active metal Au particles can be induced to preferentially expose different crystal faces. Gong et al. prepared peony-like pentahedral Al(III)-enriched alumina nanosheets for the dehydrogenation of propane by sol-gel method. 3+ The peony-shaped Al2O3 with a unique morphology and rich pentacoordinated Al2O3 was used as the support, and the effect of different contents of pentacoordinated Al2O3 on the propane dehydrogenation performance of Pt-Sn / Al2O3 catalyst was studied. 3+ The Pt-Sn / Al2O3 catalyst with a structure exhibits excellent propane dehydrogenation performance. Liu et al. in Supportmorphology-dependent alloying behavior and interfacial effects of bimetallicNi-Cu / CeO2 catalysts, Chemical Science, 2019, 10, 3556-3566 prepared a series of CeO2 with selective exposure of different crystal faces as catalyst supports based on the anisotropy of metal oxides by morphology control. The study found that the specific crystal faces of CeO2 have a significant effect on the reduction rate of the multi-metal component precursors loaded on its surface. NiCuO is easily formed on the surface of CeO2 (111) with a low concentration of coordinated unsaturated sites.x Precursor, during the reduction process, this crystal face has a considerable effect on the Ni and Cu metal precursors, resulting in matching reduction rates of the bimetallic components, so that Ni and Cu atoms simultaneously nucleate and grow and are arranged in an orderly manner. In addition to the oxide crystal face, the properties of the support such as pore structure, specific surface area, and coordination structure have a significant effect on the structure of the active metal component, which inspired us to use the coordination structure of the industrial Al2O3 support to induce the interaction between Ni and Sn, thereby obtaining a supported bimetallic M-Sn catalyst with a stable structure and a highly ordered arrangement of metal atoms.

[0004] It is well known that based on the anisotropy of oxide crystals, the exposed crystal faces can be preferentially regulated during the crystal growth process, thereby showing different properties. Crystal growth mainly includes two steps: nucleation and crystallization. The methods currently reported to regulate the crystal faces are mostly concentrated in the crystallization process. Recently, Li et al. prepared boehmite with preferential exposure of (020) crystal faces and high specific surface area by separating the nucleation and crystallization steps based on different rotation speeds of a rotating liquid film reactor in Batch and fixed-bed adsorption behavior of porous boehmite with high percentage of exposed (020) facets and surface area towards Congo red, Inorg. Chem. Front, 2021, 8, 735-745. Based on this, this work adopts the nucleation and crystallization isolation method to prepare ultra-high content of coordination-unsaturated Al2O 3-V , using it as a carrier, and using the unsaturated coordination structure on the surface of Al2O3 to induce the construction of a series of bimetallic M-Sn catalysts. By precisely controlling the number of unsaturated coordination structures on the surface of Al2O3, the reduction rate and matching degree of the M and Sn components and their interaction with the M and Sn components were controlled, thus obtaining a highly ordered arrangement of metal atoms, a specific morphology and a stable M-Sn / Al2O 3-V . Summary of the invention

[0005] The purpose of the present invention is to provide a structurally stable supported Sn-based alloy catalyst and a preparation method and application thereof. The catalyst is mainly used for selective hydrogenation of alkynes and selective dehydrogenation of alkanes, and exhibits the characteristics of high activity, selectivity and stability.

[0006] The catalyst provided by the present invention is a supported metal catalyst, represented by M-Sn / Al2O3- V, wherein M is an active metal, and the M is one of Ni, Pt, and Pd, preferably one of Ni or Pt; the loading amount of the active metal M is 1.0 to 10.0 wt%, preferably 1.0 to 5.0 wt%; the loading amount of the auxiliary metal Sn is 1.0 to 10.0 wt%, preferably 1.5 to 5.0 wt%. In Al2O3-V V Al represents a pentacoordinate structure 3+ , Al2O 3-V Represents Al2O3 with a highly unsaturated five-coordinate structure.

[0007] The structural characteristics of the catalyst are: the Al2O3-V carrier has a high content of unsaturated five-coordinated Al 3+ sites, acting as nucleation centers to capture M and Sn precursors, and unsaturated five-coordinated Al 3+ The sites interact differently with M and Sn, resulting in matching reduction rates of the bimetallic components and allowing M and Sn atoms to nucleate and grow simultaneously, forming a stable and ordered alloy structure with a specific morphology, in which the active metal M atoms are discontinuous and electron-rich.

[0008] The present invention provides a method for preparing a stable supported Sn-based alloy catalyst, and the specific steps are as follows:

[0009] A. Prepare an Al salt solution with a concentration of 1-2 mol / L using AlCl3·6H2O and deionized water, prepare an alkali solution with a concentration of 1-2 mol / L using NaOH and deionized water, start the micro liquid membrane nucleation reactor, set the stator-rotor gap of the nucleation reactor to 0.1-0.5 mm, and the rotation speed to 100-3000 rpm, add the Al salt solution and the alkali solution into the reactor at a volume ratio of 1:0.5-1 for rapid nucleation, wherein the alkali solution is appropriately excessive, and collect the nucleation slurry at the slurry outlet;

[0010] The nucleation reactor is described in patent: ZL201210105567.6.

[0011] B. The nucleation slurry of step A is transferred to a reactor, crystallized at 150-200°C for 10-30h, cooled naturally to room temperature, discharged, separated, and the obtained crystallized product is washed alternately with deionized water and ethanol until neutral, and dried at 80-100°C for 10-16h; the dried white solid is ground into powder; and heated in a muffle furnace in an air atmosphere at 1-10°C·min -1 The temperature is raised to 450-600℃ and calcined for 2-6h to obtain a high content of unsaturated five-coordinated Al 3+ The structure of Al2O3 is represented by Al2O 3-V .

[0012] Al2O 3-VThe formation mechanism is that the raw material liquid is subjected to shear force in the nucleation reactor. The magnitude of the shear force can be changed by adjusting the rotation speed, so that the crystal nucleus exhibits an unsaturated structure. On this basis, high-content coordinated unsaturated Al2O is generated through temperature-controlled crystallization. 3-V .

[0013] C. At room temperature, according to the Al2O 3-V The amount of M and Sn and the loading amount of M and Sn are determined, soluble M salt and soluble Sn salt are added into deionized water, and magnetic stirring is used to completely dissolve them to prepare an impregnation solution containing M and Sn, wherein the molar ratio of M to Sn is 1:0.2-5, and the concentration of M is 40-100 mmol / L;

[0014] Al2O 3-V Add to the impregnation solution for impregnation, where 100-300g Al2O is added per liter of impregnation solution 3-V , continue stirring at 20-40℃ for 2-5h until it becomes viscous, and dry at 80-100℃ for 10-18h, then heat in air at 2-10℃·min -1 The temperature was raised to 300-600℃ and calcined for 2-6h to obtain MO-SnO2 / Al2O 3-V Precursor;

[0015] The soluble M salt is one of Ni(NO3)2·6H2O, Pd(NO3)2, Na2PdCl4, H2PtCl6·6H2O, and the soluble Sn salt is SnCl4·5H2O or SnCl2;

[0016] D. The MO-SnO2 / Al2O 3-V The precursor was heated at 2-10℃·min in a hydrogen atmosphere. -1 The temperature was raised to 300-600 °C for reduction for 1-6 h, and then cooled to room temperature to obtain a supported bimetallic alloy catalyst with highly ordered metal atoms, specific morphology and stability, represented by M-Sn / Al2O 3-V , wherein the loading amount of the active metal M is 1.0 to 10.0 wt%, preferably 1.0 to 5.0 wt%; the loading amount of the auxiliary active metal Sn is 1.0 to 10.0 wt%, preferably 1.5 to 5.0 wt%.

[0017] Figure 1 Al2O prepared in step B of Example 1 3-V Carrier 27 Al solid NMR spectrum. It can be clearly observed from the figure that the five-coordinated Al 3+ The characteristic peaks of the species, among which the content of pentacoordinate is 20.8%, indicate that alumina contains abundant unsaturated sites.

[0018] Figure 2 Ni-Sn / Al2O prepared in step D of Example 1 3-V Scanning transmission electron microscopy (STEM) and mapping photos of the catalyst. The STEM photo shows that the active metal particles have a long strip morphology, and the positions of Ni and Sn elements in the mapping photo are highly overlapped, indicating that an ordered Ni-Sn alloy structure has been formed.

[0019] Figure 3 Ni-Sn / Al2O prepared in step D of Example 1 3-V X-ray diffraction spectrum of the catalyst. From the figure, we can observe the characteristic peaks of Ni3Sn2 ordered alloy, but not the characteristic peaks of single metal Ni and Sn, which indicates that Ni and Sn form an ordered alloy structure.

[0020] Figure 4 Ni-Sn / Al2O prepared in step D of Example 1 3-V In situ X-ray photoelectron spectroscopy (insitu XPS) of the catalyst shows that the Ni species in the Ni-Sn ordered alloy is electron-enriched.

[0021] Figure 5 Example 1 has a high content of unsaturated Al 3+ Al2O 3-V Coordination structure induced Ni-Sn / Al2O 3-V The experimental results of the catalyst in the selective hydrogenation of acetylene to ethylene reaction, A is the curve of acetylene conversion rate changing with reaction temperature, B is the curve of ethylene selectivity changing with acetylene conversion rate. When the reaction temperature is 165℃, the acetylene conversion rate is close to 100% and the ethylene selectivity is 90%.

[0022] Figure 6 Example 2 has a high content of unsaturated Al 3+ Al2O 3-V Coordination structure induced Pt-Sn / Al2O 3-V The experimental results of the catalyst in the propane dehydrogenation reaction to propylene showed that the initial conversion rate of propane at 560°C was 75%, and the propylene selectivity was 98%. After 42 hours of continuous reaction, the propane conversion rate was still as high as 43%, and the propylene selectivity was 99.5%, indicating that the catalyst has good catalytic activity and long-term stability. The loading amount of Pt is 1.0%, and the loading amount of Sn is 1.8%.

[0023] Beneficial effects of the present invention: The present invention utilizes the rapid nucleation characteristics of the micro-liquid membrane nucleation reactor to prepare a high content of unsaturated Al 3+ Al2O 3-V, using it as the capture center to load M and Sn precursor, and achieving bimetallic component reduction rate matching through reduction under the induction of the unsaturated coordination structure on the Al2O3 surface, obtaining a structurally stable M-Sn ordered alloy structure with a specific morphology, in which the active metal M atoms are discontinuous and electron-rich, solving the problem of poor catalyst stability and easy segregation due to the strong interaction between Sn and Al2O3 in the traditional impregnation synthesis scheme. The preparation conditions are mild, no surfactant needs to be added, and the process flow is simple.

[0024] The catalyst is used in the selective hydrogenation of acetylene and the dehydrogenation of propane. It has excellent activity, selectivity and long-term stability, outstanding catalytic performance and is easy to recover and reuse. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Al2O prepared in step B of Example 1 3-V Carrier 27 Al solid NMR spectrum.

[0026] Figure 2 Ni-Sn / Al2O prepared in step D of Example 1 3-V Scanning transmission electron microscopy (a) and mapping photo (b) of the catalyst.

[0027] Figure 3 Ni-Sn / Al2O prepared in step D of Example 1 3-V X-ray diffraction spectrum of the catalyst.

[0028] Figure 4 Ni-Sn / Al2O prepared in step D of Example 1 3-V In situ X-ray photoelectron spectroscopy (insitu XPS) of catalysts.

[0029] Figure 5 These are the experimental results of the Ni-Sn / Al2O3-V catalyst prepared in step D of Example 1 in the selective hydrogenation of acetylene to ethylene reaction. a is the curve showing the change of acetylene conversion rate with reaction temperature, and b is the curve showing the change of ethylene selectivity with acetylene conversion rate.

[0030] Figure 6 Pt-Sn / Al2O prepared in Example 2 3-V Experimental results of the catalyst in the propane dehydrogenation reaction to produce propylene. Figure a is the curve showing the change of propane conversion rate with reaction time, and figure b is the curve showing the change of propylene selectivity with reaction time. DETAILED DESCRIPTION

[0031] Example 1

[0032] A. Dissolve 14.500g of soluble AlCl3·6H2O in 90mL of deionized water to prepare a salt solution with a concentration of 2mol / L. Dissolve 5.520g of NaOH in 70mL of deionized water to prepare an alkaline solution with a concentration of 2mol / L. Start the nucleation reactor, set the stator-rotor gap of the nucleation reactor to 0.2mm and the speed to 1500rpm, add the above 90mL of salt solution and 70mL of alkaline solution into the reactor through the salt inlet and the alkaline inlet at a flow ratio of 9:7 for rapid nucleation, and collect the nucleation slurry at the slurry outlet;

[0033] B. The nucleation slurry obtained in step A was transferred to a reactor, crystallized at 200°C for 24 hours, cooled naturally to room temperature, the crystallized product was taken out and centrifuged, washed alternately with deionized water and ethanol until neutral, and dried in an oven at 80°C for 10 hours; the dried white solid was ground into powder and heated in air at 10°C min -1 The heating rate was raised to 550℃ and calcined for 4h to obtain a high content of unsaturated five-coordinated Al 3+ Al2O 3-V .

[0034] C. At room temperature, 0.248 g Ni(NO3)2·6H2O and 0.148 g SnCl4·5H2O were added to 10 mL deionized water, and completely dissolved under magnetic stirring to prepare an impregnation solution; the impregnation solution was added to 1 g Al2O prepared in step B. 3-V The mixture was stirred at 40 °C for 2 h until it became viscous, and then dried at 80 °C for 16 h in air at 10 °C min -1 The temperature was raised to 500℃ and calcined for 4h to obtain NiO-SnO2 / Al2O 3-V Precursor;

[0035] D. NiO-SnO2 / Al2O obtained in step C 3-V The precursor was heated at 10℃·min in 10% H2 / N2 atmosphere. -1 The temperature was raised to 500 °C for 4 h and then cooled to room temperature to obtain a Ni-Sn supported bimetallic catalyst, which is represented by Ni-Sn / Al2O 3-V The loading amounts of Ni and Sn are 5% respectively.

[0036] pass Figure 2 The characterization shows that the catalyst has a highly ordered arrangement of metal atoms, a specific morphology and a stable alloy structure.

[0037] The performance of the above catalysts was evaluated using the selective hydrogenation reaction of acetylene as a probe reaction:

[0038] 0.300g of Ni-Sn / Al2O 3-V The catalyst was mixed evenly with 1.400g of quartz sand of 40-70 mesh, and placed in the middle of a quartz tube reactor with an outer diameter of 8mm. Both ends of the catalyst were fixed with quartz wool. The reaction gas composition was 0.50% C2H2 / 5.00% H2 / 49.50% C2H4 / 1.00% C3H8 / N2 balance gas. The test was carried out under normal pressure, and the reaction gas space velocity was 9780h -1 The test temperature range is 50-170℃. The fixed bed microreactor is connected to the gas chromatograph for online analysis. The data is processed by the internal standard method. The point is measured three times at every 10℃, and the average value of the three measurements is taken as the catalytic performance data at this temperature. The results are shown in Figure 5 .

[0039] Example 2

[0040] A and B are the same as in Example 1.

[0041] C. At room temperature, 4.000g H2PtCl6·6H2O and 0.296g SnCl4·5H2O were dissolved in 10mL deionized water to prepare 77mmol / L Pt solution and 85mmol / L Sn solution, respectively, according to the active metal Pt and the auxiliary metal Sn accounting for 1.0wt.% and 1.8wt.% of the carrier mass, respectively. 0.64mL Pt solution and 1.8mL Sn solution were taken and mixed to prepare the impregnation solution. The impregnation solution was added to 1g Al2O prepared in step B. 3-V The mixture was stirred at 40 °C for 2 h until it became viscous, and then dried at 80 °C for 16 h in air at 10 °C min -1 The temperature was raised to 500℃ and calcined for 4h to obtain PtO-SnO2 / Al2O 3-V Precursor;

[0042] D. The PtO-SnO2 / Al2O3 precursor obtained in step C was heated in a hydrogen atmosphere at 10°C·min -1 The temperature was raised to 600 °C for 1 h and then cooled to room temperature to obtain a supported Pt-Sn bimetallic catalyst, which is represented by Pt-Sn / Al2O 3-V .

[0043] The performance of the above catalysts was evaluated by using the propane dehydrogenation reaction to produce propylene as a probe reaction:

[0044] 0.100 g of Pt-Sn / Al2O 3-VThe catalyst was mixed evenly with 0.900g of quartz sand of 40-70 mesh, and placed in the middle of a quartz tube reactor with an outer diameter of 8mm. Both ends of the catalyst were fixed with quartz wool. The reaction gas composition was 2.50% C3H8 / 2.50% H2 / 95% N2 balance gas. The test was carried out under normal pressure, and the reaction gas space velocity was 3000h -1 The test temperature was 560°C, and the fixed bed microreactor was connected to a gas chromatograph for online analysis. Three measurements were taken every 1 hour, and the average of the three measurements was taken as the catalytic performance data under the reaction time. The results are shown in Figure 6 .

[0045] Example 3

[0046] A. 14.500 g of soluble AlCl3·6H2O was dissolved in 90 mL of deionized water to prepare an Al salt with a concentration of 2 mol / L, and 5.520 g of NaOH was dissolved in 70 mL of deionized water to prepare an alkaline solution with a concentration of 2 mol / L. The micro liquid membrane nucleation reactor was started, and the stator-rotor gap of the nucleation reactor was set to 0.2 mm and the rotation speed was set to 2500 rpm. The salt solution and excess alkaline solution were introduced into the reactor for rapid nucleation, and the nucleation slurry was collected at the slurry outlet;

[0047] B. Transfer the nucleation slurry obtained in step A to a reactor and crystallize at 200°C for 24 hours. Cool naturally to room temperature, take out the crystallized product and centrifuge it, wash it with deionized water and ethanol until it is neutral, and dry it in an oven at 80°C for 10 hours; grind the dried white solid into powder and heat it in air at 10°C min -1 The temperature was raised to 550℃ and calcined for 4h to obtain a high content of unsaturated five-coordinated Al 3+ Al2O 3-V .

[0048] C. At room temperature, 0.149 g of soluble Ni(NO3)2·6H2O and 0.148 g of soluble SnCl4·5H2O were dissolved in 10 mL of deionized water, according to the active metal Ni and the auxiliary metal Sn accounting for 3.0 wt.% and 5.0 wt.% of the carrier mass, respectively. The solid was completely dissolved under magnetic stirring to obtain an impregnation solution. The impregnation solution was added to 1 g of Al2O 3-V The mixture was stirred at 40 °C for 2 h until it became viscous, and then dried at 80 °C for 16 h in air at 10 °C min -1 The temperature was raised to 500℃ and calcined for 4h to obtain NiO-SnO2 / Al2O 3-V Precursor;

[0049] D. The NiO-SnO2 / Al2O3 precursor obtained in step C was heated in a hydrogen atmosphere at 10°C·min-1 The temperature was raised to 500 °C for 4 h and then cooled to room temperature to obtain a supported Ni-Sn bimetallic catalyst, which is represented by Ni-Sn / Al2O 3-V .

[0050] Example 4

[0051] A and B are the same as in Example 1.

[0052] C. At room temperature, according to the active metal Pt and the auxiliary metal Sn accounting for 1.0wt.% and 3.0wt.% of the support mass, 4.000g of soluble H2PtCl6·6H2O metal salt and 0.296g of soluble SnCl4·5H2O were dissolved in 10mL of deionized water to prepare impregnation solutions with concentrations of 77mmol / L and 85mmol / L, respectively. 0.64mL of the above Pt-containing solution and 3mL of the Sn-containing solution were mixed to obtain an impregnation solution, and the obtained impregnation solution was added to 1g of Al2O prepared in step B. 3-V The mixture was stirred at 40 °C for 2 h until it became viscous, and then dried at 80 °C for 16 h in air at 10 °C min -1 The temperature was raised to 500℃ and calcined for 4h to obtain PtO-SnO2 / Al2O 3-V Precursor;

[0053] D. The PtO-SnO2 / Al2O3 precursor obtained in step C was heated in a hydrogen atmosphere at 10 °C min -1 The temperature was raised to 600 °C for 1 h and then cooled to room temperature to obtain a supported Pt-Sn bimetallic catalyst, which is represented by Pt-Sn / Al2O 3-V .

[0054] Example 5

[0055] A. 14.500 g of soluble AlCl3·6H2O and 5.520 g of NaOH were dissolved in 90 mL and 70 mL of deionized water, respectively, to prepare Al salt and alkali solutions with a concentration of 2 mol / L, the micro liquid membrane nucleation reactor was started, the stator-rotor gap of the nucleation reactor was set to 0.2 mm, and the rotation speed was set to 1000 rpm, the salt solution and excess alkali solution were introduced into the reactor for rapid nucleation, and the nucleation slurry was collected at the slurry outlet;

[0056] B and D are the same as in Example 2.

[0057] C. At room temperature, according to the active metal Pt and the auxiliary metal Sn accounting for 1.0wt.% and 1wt.% of the carrier mass respectively, 4.000gH2PtCl6·6H2O and 0.296gSnCl4·5H2O were dissolved in 10mL deionized water to prepare a Pt solution with a concentration of 77mmol / L and a Sn solution with a concentration of 85mmol / L respectively. 0.64mL of the Pt solution and 1.0mL of the Sn solution were taken and mixed to prepare an impregnation solution. The impregnation solution was added to 1g Al2O prepared in step B. 3-V The mixture was stirred at 40 °C for 2 h until it became viscous, and then dried at 80 °C for 16 h in air at 10 °C min -1 The temperature was raised to 500℃ and calcined for 4h to obtain PtO-SnO2 / Al2O 3-V Precursor;

[0058] The obtained catalyst is denoted as Pt-Sn / Al2O 3-V , the loading amounts of Pt and Sn were 1.0 wt.% and 1.0 wt.%, respectively.

Claims

1. A method for preparing a structurally stable supported Sn-based alloy catalyst, characterized in that Prepare according to the following steps: A. Prepare an Al salt solution with a concentration of 1-2 mol / L using AlCl3·6H2O and deionized water, prepare an alkali solution with a concentration of 1-2 mol / L using NaOH and deionized water, start the micro liquid membrane nucleation reactor, set the stator-rotor gap of the nucleation reactor to 0.1-0.5 mm, and the rotation speed to 100-3000 rpm, add the Al salt solution and the alkali solution into the reactor at a volume ratio of 1:0.5-1 for rapid nucleation, wherein the alkali solution is appropriately excessive, and collect the nucleation slurry at the slurry outlet; the nucleation reactor is described in patent: ZL201210105567.6; B. The nucleation slurry of step A is transferred to a reactor, crystallized at 150-200°C for 10-30h, cooled naturally to room temperature, discharged, separated, and the obtained crystallized product is washed alternately with deionized water and ethanol until neutral, and dried at 80-100°C for 10-16h; the dried white solid is ground into powder; and heated in a muffle furnace in an air atmosphere at 1-10°C·min -1 The temperature is raised to 450-600℃ and calcined for 2-6h to obtain a high content of unsaturated five-coordinated Al 3+ Al2O3 of structure, expressed as Al2O 3-V ; C. At room temperature, according to the Al2O 3-V The amount of M and Sn and the loading amount of M and Sn are determined by using soluble M salt, soluble Sn salt and deionized water to prepare an impregnation solution containing M and Sn, wherein the molar ratio of M to Sn is 1:0.2-5, and the concentration of M is 40-100 mmol / L; Al2O 3-V Add to the impregnation solution for impregnation, where 100-300g Al2O is added per liter of impregnation solution 3-V , continue stirring at 20-40℃ for 2-5h until it becomes viscous, and dry at 80-100℃ for 10-18h, then heat in air at 2-10℃·min -1 The temperature was raised to 300-600℃ and calcined for 2-6h to obtain MO-SnO2 / Al2O 3-V Precursor; The soluble M salt is one of Ni(NO3)2·6H2O, Pd(NO3)2, Na2PdCl4, H2PtCl6·6H2O, and the soluble Sn salt is SnCl4·5H2O or SnCl2; D. The MO-SnO2 / Al2O3-V precursor obtained in step C was heated at 2-10°C·min in a hydrogen atmosphere. -1 The temperature was raised to 300-600℃ and reduced for 1-6h, and then cooled to room temperature to obtain M-Sn / Al2O 3-V , wherein the loading amount of the active metal M is 1.0 to 10.0 wt%; the loading amount of the auxiliary active metal Sn is 1.0 to 10.0 wt%; The loading amounts of M and Sn are respectively M and Sn in Al2O 3-V The mass percentage.

2. The method for preparing a structurally stable supported Sn-based alloy catalyst according to claim 1, wherein the loading amount of the active metal M in step D is 1.0-5.0 wt%; and the loading amount of the auxiliary active metal Sn is 1.5-5.0 wt%.

3. A structurally stable supported Sn-based alloy catalyst prepared by the method according to claim 1, characterized in that The catalyst is denoted as M-Sn / Al2O 3-V , wherein M is an active metal, which is one of Ni, Pt, and Pd; the loading amount of M is 1.0 to 10.0 wt%; the loading amount of the auxiliary active metal Sn is 1.0 to 10.0 wt%; Al2O 3-V middle V Al represents a pentacoordinate structure 3+ , Al2O 3-V It represents Al2O3 with an unsaturated five-coordinate structure; M and Sn are ordered alloy structures with specific morphology, and the active metal M atoms are discontinuous and electron-rich.

4. The structurally stable supported Sn-based alloy catalyst according to claim 3, characterized in that: The M is Ni or Pt; the loading amount of M is 1.0-5.0wt%; the loading amount of Sn is 1.5-5.0wt%.

5. An application of the structurally stable supported Sn-based alloy catalyst according to claim 3, characterized in that The catalyst is mainly used for selective hydrogenation of alkynes and selective dehydrogenation of alkanes.